HPLC and GC-MS analyses of phytochemicals from Ficus carica leaf extract and essential oil along with their antimicrobial properties - Maximilian Lackner; Abdelfattah Z.M. Salem; Mohamed Z.M. Salem; Abeer A. Mohamed; José Luis Ponce-Covarrubias; Shady Selim (Journal of Agriculture and Food Research)
Ficus carica L. (Common Fig) is one of the oldest shrubs useful to mankind, belonging to the Moraceae family. It offers nutritional and medical benefits as a source of potentially bioactive chemicals. This work used fig leaves to obtain acetone extract (ACE) and essential oil (EO). The ACE and the EO were evaluated for antibacterial activity against bacterial wilt and soft rot of potato caused by Ralstonia solanacearum LN827661 and Pectobacterium carotovorum LN851554, respectively, and evaluated for antifungal activity against cucumber grey mold fungi caused by Botrytis cinerea PP758474 and early blight of tomato caused by Alternaria alternata PP737871. The chemical compounds in the ACE were analyzed using gas chromatography-mass spectrometry (GC-MS) and high-performance liquid chromatography (HPLC-DAD (diode-array detector)), while the GC-MS was used to analyze the chemical compounds in the EO. The main phenolic compounds in the ACE were p-coumaric acid (13.63 μg/mL), ferulic acid (12.63 μg/mL), and caffeic acid (10.42 μg/mL), and the main flavonoid compounds were naringin (15.45 μg/mL), rutin (8.60 μg/mL), and luteolin (7.48 μg/mL). The main compounds in the ACE from F. carica leaves by GC-MS were bergapten (22.10 %), linolenic acid (19.47 %), 2,8-diiododibenzofuran (5.77 %), and ficusin (5.56 %). The abundant compounds in the EO were versalide (12.88 %), isopropyl myristate (12.68 %), α-hexyl cinnamaldehyde (4.65 %), lilial (4.33 %), and tetradecane (4.04 %). The EO at 2000 μL/mL exhibited the maximum activity against P. carotovorum with an inhibition zone (IZ) value of 15.66 mm. This was followed by the ACE at 2000 μg/mL with IZ value of 14.66 mm. The highest activity against the growth of R. solanacearum was found by the EO (2000 μL/mL) and the ACE (2000 μg/mL) with IZ values of 16.66 mm and 15.33 mm, respectively. The EO at 2000 μL/mL and 1000 μL/mL showed the highest fungal inhibition percentage (FIP) against A. alternata growth, with values of 47.46 % and 38.83 %, respectively. Concerning B. cinerea growth, the EO recorded the highest FIP values of 56.33 and 52.93 % at 2000 and 1000 μL/mL, respectively. This work highlights the potential of side stream valorization from fig production to obtain safe and sustainable antimicrobial agents for crop protection, amongst them potatoes, tomatoes, and cucumber.